Technologies for Distributed Generation: key performance factors for industrial application - G. G. Nalbandyan; S. S. Zholnerchik (Стратегические решения и риск-менеджмент)
The reduction in the cost of technologies for distributed generation involves an increasing decentralization of power generation and large-scale development of distributed sources around the world. This trend is a key change in both the characteristics of electricity consumption: it is becoming increasingly flexible and mobile, and the patterns of consumer behavior in the electricity market. Electricity consumers are becoming at the same time its suppliers and require revision of traditional regulation standards of the electricity market. The purpose of the article is to assess the influence of distributed generation on the economy of both enterprises and the country as a whole. To identify the effects of the introduction of distributed generation technologies, the method of case study analysis is used. The empirical analysis was carried out on the basis of twelve Russian companies that use their own energy sources. The selected companies belong to the following industries: industrial production, housing and communal services, retail trade, construction, agriculture. Technological and economic effects are revealed. Technological ones include: improving consumer reliability, energy security, involving local energy resources, optimizing load management and redundancy, providing the flexibility of smart grids (in terms of generation), reducing the load on the environment, including CO2 emissions. Economic effects: optimization of the load schedule, reduction of losses in the process of transmission/distribution of energy, expansion of cogeneration, etc., providing the consumer with the electricity of a given quality, saving losses in networks, reducing the cost of energy. The identified effects of the introduction of distributed generation technologies make it possible to highlight the advantages of regeneration facilities: high efficiency and the possibility of cogeneration and trigeneration, individual maneuvering capacity loading, high reliability of equipment, low cost of transportation of electricity, fuel usage of the by-products and the main production waste. In conclusion, recommendations are formulated on a set of measures for the development of industrial distributed generation in Russia at the Federal level.